Redução de NO com CO sobre catalisadores de CuO, Fe2O3 e CuO-Fe2O3 suportados em TiO2, ZrO2 e TiO2-ZrO2 - efeito do vapor de água na atividade e seletividade a N2 - Nova Castelblanco, William (Universidade Federal de São Carlos, 2013)
The combustion of petroleum fuels produces large emissions of NOX, SOX and other strong atmospheric pollutants. The abatement of NOX can be achieved by the nonselective catalytic reduction of NO with CO, for that, supported noble metals have been the most commonly used, with high cost as disadvantage. Transition metal oxides show good activity for this reaction, however, they have poor performance in the presence of SO2, O2 and water steam. Thus, this study aimed to prepare, characterize and evaluate catalysts based on CuO, Fe2O3 and CuO-Fe2O3 supported on TiO2, ZrO2 and their mixtures, in the reduction of NO to N2 with CO in the presence or absence of water steam. XRD data, N2 adsorption and H2-TPR showed that mixed oxides and their catalysts, prepared by sol-gel in-situ, presented specific surface areas between 30 to 60 m2/g, with Cu or Fe species highly distributed, having the last greater interaction with titanium. Rietveld refinement showed preferential formation of zirconium titanate, then showing a close interaction of these species in the mixed supports. All catalysts were highly active in the reduction of NO to N2. At temperatures below 500 °C a CuO catalysts were more active and selective for the formation of N2 than Fe2O3, with the formation of N2O being favored with the increase of zirconium in the support. At 600 °C, the high conversion of NO to N2 on CuO was not influenced by the content of TiO2 in the support. Also at 600 °C, an increasing in the content of titanium in the Fe2O3 catalysts resulted in a significant drop in the conversion of NO to N2. The presence of water steam during the reduction of NO with CO at 600 °C caused a significant decrease in the conversion of NO to N2 and CO to CO2 on the CuO catalyst on the support with higher titanium content. The water steam completely eliminates the activity for the reduction of NO to N2 on Fe2O3 catalysts, but keeping a high conversion of CO to CO2. The CuO and CuO-Fe2O3 catalysts on zirconium-rich supports showed high potential for the abatement of NOX in the presence of water steam at temperatures above 500 ºC.
Keywords: Catálise heterogênea; Redução de NO; Abatimento de NO/CO; Óxido de ferro; Óxidos mistos; CO; CuO; Fe2O3; TiO2; ZrO2; NOX reduction; Water steam; ENGENHARIAS::ENGENHARIA QUIMICA